Nutritional Biomarkers for Predicting Pancreatic Beta Cell Failure in Central Obesity - Miftakh Nur Rahman; Ajeng Diantini; Miswar Fattah; Melisa Intan Barliana (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: There is a continuous rise in the prevalence of central obesity and become a pressing health problem in the world. Central obesity followed by many metabolic disorders especially Type 2 Diabetes Mellitus (T2DM). The pathogenesis started from overnutrition signal that force pancreatic beta cells to produce a large number of insulin. Low-grade chronic inflammation that occurred also affects the organs sensitivity against insulin and caused beta cells to compensated this situation and at the end become exhausted and loss its function.CONTENT: Along compensation mechanism, certain nutrients were support the beta cells to maintain their mass and function to produce insulin. Short chain fatty acids (SCFAs) are gut microbiota fermentation product that act as nutrient and give an advantage to the proliferation and survivability of the beta cells. Zinc (Zn) also plays an important role in every step of insulin production. Moreover, these nutrients protecting pancreas against inflammation and oxidative stress through certain mechanism. Most of patients with central obesity are unaware of the presence of this disturbance at early stage. Whereas, at molecular level there is a magnitude of SCFAs and Zn level in the blood that would become an early signal and predict the damage of beta cells.SUMMARY: Quantification of these two nutrients in the blood expected to provide an early warning tool to maintain insulin adequacy and predict the possibility of beta cell failure in central obesity with promising performance.KEYWORDS: central obesity, T2DM, SCFAs, Zinc, beta cell failure